The Role of Employee Stock Option Plan to Reduce Earnings Management Actions - Namla Elfa syariati; Bambang Subroto; Wuryan Andayani (Jurnal Keuangan dan Perbankan, 2017)
This research aimed to investigate the influence of earnings management to the compensation of the Employee Stock Option Plan (ESOP). Taking agency theory to explain theconflict between managers and shareholders. It was expected that ESOP would increasethe managerial responsibility to companies, but the managers have abused it to gainmore benefits for themselves. This research used simple linear regression and multiplelinear regression analysis with a sample of 120 publicly traded companies listed on theStock Exchange during 2011-2014. This study had one independent variable (ESOP) and controls four variables (managerial ownership, institutional ownership, the board of directors and audit committees). The result of this study was that earnings management had a positive impact on improving employee compensation due to the ESOP program. The existenceof managerial ownership and commissioners could reduce earnings managementactions in the implementation of the ESOP.DOI: https://doi.org/10.26905/jkdp.v21i3.1281